Interrater reliability of client categorization system as a psychiatric status rating scale in measuring psychiatric patients’ health status - Nurjannah, Intansari; Nurmasari, Putri; Nugraha, Irwan Tri; Katan, Diki Yuge; Hariyadi, Ki (International Journal of Research in Medical Sciences, 2017)
Background: Reliable instrument is needed by nurses to measure patient’s status. This study aimed to determine the interrater reliability of client categorization system instrument used in psychiatric setting. Methods: Data was collected two periods in a year by twelve raters. They used the CCS to simultaneously gauge the condition of 30 patients for 98 measurements. Data was analyzed using the Cohen’s-Kappa formula and percent agreement. Results: The analysis showed that the Cohen-Kappa values of interrater reliability were 0.59 which can be categorized as moderate (accepted, if value >0.41) and percent agreement value was 77.78% indicated acceptable. Conclusions: The CSS has moderate and acceptable category of interrater reliability and can be recommended for use in clinical practice.